Elderly in a country going through epidemiological health transition - The example of Thailand - P. Pongpaew (2018)
A review of the available literature on the socio-economic-, health- and nutritional status of elderly in Thailand showed that the majority of individuals in this age group is still quite well-off. The fact that over 80% of them are living with their families puts them in a better social environment than their counterparts in western countries. The health- and nutritional status of most elderlys, with the exception of their vitamin status, is quite good. Biochemical indicators and intake data show deficiencies over a wide range for different vitamins. However, clinical signs of vitamin deficiencies are rare. Changes in the country's socio-economic environment and the increasing proportion of elderly people will challenge the health delivery sector to pay more attention to the care and service for the elderly in the future.